(untitled) (Journal of Humanities and Social Sciences Research, 2023)
This study included effective leadership as an independent variable with its sub-dimensions (subjective skills, intellectual skills, human skills, technical skills ) The Faculty of Dentistry at Tikrit University has been selected as a research community that has adopted the opinions of the senior departments of the dean, his assistants, heads of departments, officials of divisions and units, and the number of (52) directors, where the relationship and impact between the independent variable effective leadership in its four dimensions and the dependent variable job security are tested ، The questionnaire was used as a data collection tool, where ( 52 ) forms were distributed for the research sample, a comprehensive inventory sample was used , and ( 49) workable forms were recovered. the main research hypothesis was that there is a correlation and a moral impact between effective leadership and job security، The data were analyzed using the spss program, as a number of statistical methods were used to investigate the validity of the hypothesis, including the correlation coefficient (person) and simple regression analysis, where the results matched the research hypothesis, it was found that there is a correlation and a moral impact between effective leadership and job security, so several recommendations were formulated that it is hoped that those concerned will benefit from the current study.